2005
DOI: 10.1111/j.1523-1739.2005.00045.x
|View full text |Cite
|
Sign up to set email alerts
|

Edge Influence on Forest Structure and Composition in Fragmented Landscapes

Abstract: Although forest edges have been studied extensively as an important consequence of fragmentation, a unifying theory of edge influence has yet to be developed. Our objective was to take steps toward the development of such a theory by (1) synthesizing the current knowledge of patterns of forest structure and composition at anthropogenically created forest edges, (2) developing hypotheses about the magnitude and distance of edge influence that consider the ecological processes influencing these patterns, and (3)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

40
1,020
5
107

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 1,117 publications
(1,214 citation statements)
references
References 57 publications
40
1,020
5
107
Order By: Relevance
“…The edge, as an environment with higher light intensity, dryer air and moderately strong wind blowing through the branches, sustained approximately 4.6 times less biomass than the 60-m transect and 3.3 times less than did the 10-m and 30-m transects, a result that agrees with the findings of Williams-Linera (1990), who reported that the most significant changes occur at 2.5-15 m in from the edge of the fragment.. Biomass is related to primary production, niches diversity and the carrying capacity of the ecosystems (Cardinale et al 2006). In the present study, two factors contributed to this: large species occurred less frequently at the edge; and the individuals at the edge tended to be smaller than those of the same species in inner transects what somehow agrees with other studies (Harper et al 2005) that described greater growth and recruitment of some species but reduced growth or increased mortality of others.…”
Section: Discussionsupporting
confidence: 81%
“…The edge, as an environment with higher light intensity, dryer air and moderately strong wind blowing through the branches, sustained approximately 4.6 times less biomass than the 60-m transect and 3.3 times less than did the 10-m and 30-m transects, a result that agrees with the findings of Williams-Linera (1990), who reported that the most significant changes occur at 2.5-15 m in from the edge of the fragment.. Biomass is related to primary production, niches diversity and the carrying capacity of the ecosystems (Cardinale et al 2006). In the present study, two factors contributed to this: large species occurred less frequently at the edge; and the individuals at the edge tended to be smaller than those of the same species in inner transects what somehow agrees with other studies (Harper et al 2005) that described greater growth and recruitment of some species but reduced growth or increased mortality of others.…”
Section: Discussionsupporting
confidence: 81%
“…Ainda nas áreas de borda são observadas alterações a níveis de temperatura; de velocidade e turbulência do vento; e de umidade relativa do ar, bem como de umidade do solo, os quais estão relacionados às mudanças e perdas que ocorrem na composição e estrutura da vegetação (FRANCESCHINELLI et al, 2003;HARPER et al, 2005;OLIVEIRA et al, 2004). Com isso, objetivou-se neste trabalho, avaliar efeito de borda sobre o componente arbóreo, adulto e regenerante, em dois fragmentos de Floresta Atlântica, na Bacia do Rio Tapacurá -PE.…”
Section: Introductionunclassified
“…In particular, the shallow soils (siliceous, rocky and skeletal) and the effects of strong winds, such as increased evapotranspiration and air turbulence (Harper et al 2005) are among the most limiting environmental factors. Aridity and wind speeds are expected to be higher in these marginal sites, affecting tree health through drought and mechanical damage (Barbeta et al 2011).…”
Section: Effects Of Coppicing and Habitat On Beech Health In Sicilymentioning
confidence: 99%
“…Indeed, Mediterranean mountain beech stands located on ridges or steep slopes, as well as those that are in fragmented stands or near edges, are negatively affected by the increased exposure to wind, turbulence, warmer air and higher soil temperatures (Harper et al 2005, Heithecker & Halpern 2007, Barbeta et al 2011.…”
Section: Introductionmentioning
confidence: 99%